Fast burn - Foster, Lori, 1958- (Foster, Lori, 1958- Body Armor novel., 2018)
"The moment Brand Berry meets beautiful, driven Sahara Silver, the connection between them is electric. It's also something he can't pursue. Sahara wants him, sure--to join Body Armor, where his MMA skills, size, and cocky attitude make him perfect for her elite crew of bodyguards. For Sahara, the agency always comes first, and Brand needs more. Yet when she's kidnapped by men searching for her missing brother, he doesn't hesitate"--Amazon.com.